A Study on Availability of Basic Civic Facilities in Urban Slum Area of Bhuj, Gujarat, India - Bipin Prajapati; Kavita Benker; K N Sonalia; Nitiben Talsania; Siddharth Mukherjee; K N Trivedi (Medsci Publications, 2011)
Background: In cites of India, there is around 50-60% of the population of the urban areas that lives in urban slums where basic facilities such as water, sanitation, health, electricity etc are poor. Disease morbidity and mortality is high due to poverty, poor nutrition and poor education and children living on payments slum are more exposed to drug abuse, child labour and sexual exploitation. Objective: To study the availability of basic civic facilities in urban slums in bhuj city. Materials and Methods: A cross sectional study was carried out between january 2011 to june 2011 on randomly selected 109 households at ramdevnagar (urban slum) area located in the western part of bhuj. House to house survey was carried out and information was obtained on predesigned and pretested proforma by interviewing the head and or other members of family. Family details, ration card, election card, water,gutterline, waste disposal, electric connection, education, availability of basic health facility were included in the proforma. The data were analyzed in microsoft excel. Results: 50.4% houses are permanent, 73% are having BPL ration card, 5.5 % houses is having municipality water line connection, no house is having gutter connection and 58.7% houses are having electricity connection, 60% houses don't have toilet facility, No houses have the facility of dumping solid waste. lack of basic infrastructure and primary health facilities in this area. Conclusion: There are infrastructural issues like lack of permanent road, street light, dumping of solid waste, drinking water facility and drainage of waste water facility. Proper implementation of stretegy of town planning. Improve the efficiency of public health system in the cities by strenghthing , revamping and rationalizing urban primary health structure.